MMS Multipoint electric field observations of small‐scale magnetic holes. Issue 12 (20th June 2016) - Goodrich, Katherine A.; Ergun, Robert E.; Wilder, Frederick D.; Burch, James; Torbert, Roy; Khotyaintsev, Yuri; Lindqvist, Per‐Arne; Russell, Christopher; Strangeway, Robert; Magnes, Werner; Gershman, Daniel; Giles, Barbara; et al.
Abstract: Small‐scale magnetic holes (MHs), local depletions in magnetic field strength, have been observed multiple times in the Earth's magnetosphere in the bursty bulk flow (BBF) braking region. This particular subset of MHs has observed scale sizes perpendicular to the background magnetic field ( B ) less than the ambient ion Larmor radius ( ρ i ). Previous observations by Time History of Events and Macroscale Interactions during Substorms (THEMIS) indicate that this subset of MHs can be supported by a current driven by the E × B drift of electrons. Ions do not participate in the E × B drift due to the small‐scale size of the electric field. While in the BBF braking region, during its commissioning phase, the Magnetospheric Multiscale (MMS) spacecraft observed a small‐scale MH. The electric field observations taken during this event suggest the presence of electron currents perpendicular to the magnetic field. These observations also suggest that these currents can evolve to smaller spatial scales. Key Points: MMS shows multipoint electric field observations of a small‐scale magnetic hole Electric field observations suggest small‐scale magnetic holes are supported by perpendicular electron currents MMS observations suggest that small‐scale magnetic holes can cascade to smaller spatial scales